Spin–orbit coupling in silicon for electrons bound to donors. (December 2018) - Weber, Bent; Hsueh, Yu-Ling; Watson, Thomas; Li, Ruoyu; Hamilton, Alexander; Hollenberg, Lloyd; Rahman, Rajib; Simmons, Michelle
Abstract Spin–orbit coupling (SOC) is fundamental to a wide range of phenomena in condensed matter, spanning from a renormalisation of the free-electrong -factor, to the formation of topological insulators, and Majorana Fermions. SOC has also profound implications in spin-based quantum information, where it is known to limit spin lifetimes (T 1 ) in the inversion asymmetric semiconductors such as GaAs. However, for electrons in silicon—and in particular those bound to phosphorus donor qubits—SOC is usually regarded weak, allowing for spin lifetimes of minutes in the bulk. Surprisingly, however, in a nanoelectronic device donor spin lifetimes have only reached values of seconds. Here, we reconcile this difference by demonstrating that electric field induced SOC can dominate spin relaxation of donor-bound electrons. Eliminating this lifetime-limiting effect by careful alignment of an external vector magnetic field in an atomically engineered device, allows us to reach thebulk-limit of spin-relaxation times. Given the unexpected strength of SOC in the technologically relevant silicon platform, we anticipate that our results will stimulate future theoretical and experimental investigation of phenomena that rely on strong magnetoelectric coupling of atomically confined spins. Spins in silicon: back to the bulk The lifetime of electron spins bound to phosphorous donors in nanoelectronic silicon devices can be restored to bulk values by suppressing spin–orbit coupling. An international collaboration led by Michelle Simmons of the University of New South Wales, Australia, have measured the lifetimes of a donor-bound spin within a silicon nanoelectronic device, and found it to be of the order of seconds—substantially shorter than in bulk, where the lifetime is on the order of minutes. This difference was found as due to a spin–orbit-induced magnetoelectronic coupling, which impacts spin lifetime and coherence. By countering this effect through a carefully aligned external magnetic field, the researchers could restore the lifetime of the spins in the device to bulk values, which will be helpful in improving performances of quantum devices.